2009
DOI: 10.1016/j.cca.2009.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of matrix metalloproteinase (MMP)-8, MMP-9, and pro-inflammatory markers in patients with metabolic syndrome

Abstract: Patients with MetS have increased circulating concentrations of pro-MMP-9, MMP-8, and TIMP-1 that are associated with increased concentrations of pro-inflammatory mediators and adhesion molecules. These findings suggest that MMPs may have a role in the increased cardiovascular risk of MetS patients. Pharmacological interventions targeting MMPs, especially MMP-9 and MMP-8 deserve further investigation in MetS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 44 publications
8
58
2
Order By: Relevance
“…Although little is known about the biological effects of MMP-8, some studies have shown elevated levels of MMP-8 in subclinical and clinical atherosclerosis [13], unstable angina [22], metabolic syndrome [12], and childhood obesity [23]. Conversely, reduced levels of MMP-8 were associated with diastolic heart failure [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although little is known about the biological effects of MMP-8, some studies have shown elevated levels of MMP-8 in subclinical and clinical atherosclerosis [13], unstable angina [22], metabolic syndrome [12], and childhood obesity [23]. Conversely, reduced levels of MMP-8 were associated with diastolic heart failure [24].…”
Section: Discussionmentioning
confidence: 99%
“…The current study was delineated to exclude clinical conditions and pharmacotherapeutic factors, such as hypertension, diabetes, cardiovascular disease, use of statins, and smoking, that may affect the MMP and TIMP-1 levels [5,8,12,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP9, which is released from adipose tissue (Bouloumie et al 2001), is a key enzyme involved in these processes. Higher plasma and tissue MMP9 levels are found in obese subjects (Laimer et al 2005) and patients with the metabolic syndrome (Goncalves et al 2009). In this study, the NOD1 ligand induced MMP9 gene expression and secretion of pro MMP9 from both subcutaneous and omental adipose tissues.…”
Section: Figurementioning
confidence: 99%
“…12,13,[28][29][30] While there is evidence that MMPs in erectile dysfunction JJ Muniz et al patients with ED are more likely to have the vascular alterations commonly found in cardiovascular diseases, 2,4-9 especially among diabetics, 4-6,10,11 our findings showed similar net MMP-2 and MMP-9 activities in ED patients and in healthy controls, thus suggesting that these enzymes may not be involved in ED. Importantly, MMPs levels were carefully assessed by two independent, different techniques in the present study, thus minimizing the probability of analytical limitations.…”
Section: Discussionmentioning
confidence: 41%